PENINGKATAN MUTU PENDIDIKAN MELALUI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Sumarno, Sumarno; Saputra, Alan Luthfi Gesang (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Improving the quality of education is an orientation for the development of national civilization as an investment in the long-term future development of the nation. Currently, schools have entered the era of the industrial revolution, of course the quality of schools needs to be improved, so the leadership of school principals is needed to face this era. The principal is the leader of the school and is the person who has authority within the school. Ideal leadership is leadership that follows the demands of the industrial revolution 4.0. Leaders who follow technological developments, leaders must have skills in influencing, encouraging, guiding, directing and mobilizing other people who are related to the implementation and development of education and teaching in the era of the industrial revolution 4.0. The aim of this research is to determine the leadership of school principals in facing changing times, especially in the 4.0 era and to explain studies on the concept of leadership in facing the 4.0 era. The method used is a qualitative method. The results of the discussion can be concluded that the leadership of school principals must be able to master the technological fields that are needed today in the era of the digital revolution 4.0 to improve and explore the potential that exists within themselves and the need for the readiness of school principals to face challenges in the current era of the digital revolution 4.0.